CHARACTER VALUES ANALYSIS OF STUDENTS’ ENGLISH HANDBOOK THINK GLOBALLY ACT LOCALLY - M. Happy Nur Tsani (ELP (Journal of English Language Pedagogy), 2020)
Character building is major issue in education. The concept of national character building refers to an effort to build nation’s character as stated in National Education system Decree Number 20 of 2003 chapter 3. National education aims to develop life skill and good character building of human. Thus, as compulsory and newly published handbook with regards to the implication of 2013 Curriculum, the ninth grade students’ handbook Think Globally Act Locally should promote character values. This study aimed at exploring character values promoted in the handbook. The document analysis as one of branches in qualitative method is used in this study. The finding of this study reveals that the handbook has already promoted national character building.